Sales, parts, and service performance evaluation tool - Schieltz, Travis (Kansas State University, 2016)
For the past couple years, farm income has declined due to lower prices for corn, soybeans, and wheat. This decline has caused agricultural producers to keep equipment longer, which has affected equipment sales at John Deere. When times are good, producers buy new and trade used equipment, but when a producer’s profit is lower than previous years, they tend to save their money for input costs for the next growing season. The decline in farm income has had a negative effect on agriculture sales, but dealers can maintain their market share goals and still be profitable if they adjust their focus to other areas of their business, including sales of parts and equipment service. The goal of this study is to create an analysis tool that field managers can use to help dealers see the potential sales, profit, and pay for performance that they are missing because they are not up to suggested guidelines for sales of parts and equipment service. The tool includes several metrics from an existing report called the Categorization Report. These metrics are Dealer Performance Market Share, Aftermarket Performance Factor, Service Market Performance Factor, and Net Operating Return on Sales. The tool calculates the differences between the dealer metrics and John Deere metrics. Further, this tool is used to compare an individual dealer to other dealer averages and determine what a high performance, fully optimized dealer looks like and how much more a dealership could be selling in sales, parts and service to be a sustainable business in today’s economy. The tool is used to examine three scenarios to demonstrate its flexibility. These scenarios include a top-ten dealer, a large-scale above-average dealer, and a merger of three dealerships. The spreadsheet tool will display a two-page summary that shows how a dealership compares with other dealers that are similar in size and how they compare to the top-ten elite dealers in their category. The summary will also include market share maps to show which dealer-specific geographical areas need improvement to earn more sales in the future.
Keywords: Market share; Service profitability; Parts profitability; Performance; Evaluation tool; Implement